Contact-lens-related microbial keratitis: case report and review - Eltis, Mark (2012)
Bacterial keratitis is a serious, potentially blinding, complication most often involving overnight contact lens wear. This case report reviews the management of a patient with bacterial keratitis and discusses the etiology, differential diagnosis, classification and risk factors associated with the condition.